A Space for the Subject: Tracing Garden Culture in Muslim Russia - Bustanov, Alʹfrid Kašafovič ca. 20./21. Jh. (Journal of the economic and social history of the Orient, 2022)
This article examines the place occupied by garden culture in the mental landscape of Russia’s Muslims from the early nineteenth century to the late Socialist era. First taken from the Qur’an as a symbol of eternal salvation, the idea that gardens might embody both aesthetic and metaphysical values was further articulated by traveling missionaries with Sufi affiliations. This idea was afterwards absorbed by the generation of students graduated from Central Asian madrasas who, in the first half of the nineteenth century, brought the fashion for having gardens back to their home villages in European Russia. Gardens built or imagined by Muslims in European Russia had a history of their own, developing from the classical vision of heavenly gardens in Qur’anic exegesis into what became a central spatial category in Sufi tradition. In post-war Soviet Russia a place of piety was rethought as dacha—the entire process reflecting the evolution of Muslim subjectivity over the last few centuries.